Late Cretaceous through Cenozoic climate change on Antarctica: A view from the deep sea - Joseph, Leah Helen; University of Michigan (2001)
The climatic evolution of Antarctica is intimately linked with global climate through the processes of oceanic and atmospheric circulation. Analyses and understanding of different climatic states in the past enable a better understanding of processes that control climate and the likely impact of future climate change. The climatic evolution of Antarctica and its association with the surrounding oceanic circulation are determined using sediment parameters in cores from around Antarctica. These measures include terrigenous flux rates and grain size analysis, bulk magnetic susceptibility values, and magnetic fabrics, measured in samples obtained from Ocean Drilling Program cores that surround Antarctica.
Samples extend through the latest Cretaceous and span the time period from before ice formation occurred on Antarctica in the Cretaceous through the onset of modern conditions. Sites analyzed include the Maud Rise in the southern Atlantic Ocean, Kerguelen Plateau in the southern Indian Ocean, and Rekohu Drift in the southwestern Pacific Ocean. Results indicate that Antarctic climate between late Cretaceous to middle Eocene oscillated between wet and dry periods (although not desert-like), and paralleled changes in global climate. The middle Eocene to middle Oligocene period encompassed the first episode of major ice growth on Antarctica, beginning at ~36 Ma, reaching the continental margin ~34 Ma, and remaining unstable until 30 Ma.
This time period is representative of the evolution of the proto-Antarctic Circumpolar Current (ACC), the opening of the Tasman seaway, and subsequent thermal isolation of Antarctica; the Drake Passage opened to allow at least surface circulation by ~32 Ma. The ACC and thermohaline circulation established their present configuration by approximately 23 Ma, resulting in scouring and/or large sediment accumulations by the Pacific Deep Western Boundary Current. Fluctuations related to the intensity of bottom water formation, reflecting Antarctic climate, are recorded during this time, including major growth of the East Antarctic Ice Sheet between 14-11 Ma and the initial formation of the West Antarctic Ice Sheet at ~10 Ma. The East Antarctic Ice Sheet exhibited fluctuations from at least 6.4 Ma until ~4 Ma. Significantly, the stable cold-based ice sheet becomes established after 4 Ma, during a period of global warmth.
(UnM)AAI3029355
Source: Dissertation Abstracts International, Volume: 62-10, Section: B, page: 4427.
Co-Chairs: David K. Rea; Ben A. van der Pluijm.
Thesis (Ph.D.)--University of Michigan, 2001.
Microfiche.
Keywords: Geology